2019
DOI: 10.1080/17482631.2019.1632111
|View full text |Cite
|
Sign up to set email alerts
|

From being restrained to recapturing vitality: non-western immigrant women’s experiences of undergoing vitamin D treatment after childbirth

Abstract: Forss (2019) From being restrained to recapturing vitality: nonwestern immigrant women's experiences of undergoing vitamin D treatment after childbirth,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Serum 25(OH)D was measured at baseline and after three months treatment with participants who reported improved pain scores (visual analog scale) and muscle strength once serum 25(OH)D normalized [ 36 ]. A follow-up qualitative study conducted on a subsample of these same women in the clinical trial ( n = 6) reported these themes following supplementation: living a restrained life prior to treatment, recaptured vitality after treatment, and the need for continuity in medication [ 37 ]. This study provides some evidence that vitamin D supplementation may be a potential treatment for pregnant women, particularly Black and Hispanic women, who have deficient levels of serum 25(OH) D to address potential ailments such as back pain and poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Serum 25(OH)D was measured at baseline and after three months treatment with participants who reported improved pain scores (visual analog scale) and muscle strength once serum 25(OH)D normalized [ 36 ]. A follow-up qualitative study conducted on a subsample of these same women in the clinical trial ( n = 6) reported these themes following supplementation: living a restrained life prior to treatment, recaptured vitality after treatment, and the need for continuity in medication [ 37 ]. This study provides some evidence that vitamin D supplementation may be a potential treatment for pregnant women, particularly Black and Hispanic women, who have deficient levels of serum 25(OH) D to address potential ailments such as back pain and poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%